Through A Glass Darkly The Many Sides of Paul Taylor's Choreography - Kane, Angela (Edinburgh: Edinburgh University Press, 2003)
RESUMEN: The excitement and intrigue of working with primary dance resources was first revealed to me when Clement Crisp hired me to undertake archive research for his co-authored book, London Contemporary Dance Theatre: The First 21 Years (with Mary Clarke) during the late-1980s. Previously, I had been inspired by his dance history classes at the Laban Centre and it was through his encouragement that I began to write for The Dancing Times and other periodicals. This second Jubilee issue, celebrating 50 years of Clement's writing, is a fitting occasion for me to acknowledge his support and enthusiasm over the years. Dance's supreme world-smith, wit and bon vivant, it was through his not-too-subtle prodding during the early 1990s that I came to pursue doctoral research into Paul Taylor's choreography. One of the main aims of my thesis was to challenge the over-simplistic classification of Taylor's work into "light" and/or "dark" categories and, through analysis of different structural and thematic forms, to propose instead an alternative and more open approach to reading Taylor's dances. What follows is a revised version of the penultimate chapter of my doctoral thesis. Thank you, Clement: but for whom...! I would also like to thank Taylor company dancer, Orion Duckstein, for allowing me to use photographs from his personal collection to accompany this article and to Terence Kane for his technical help with all things photographic.